2015
DOI: 10.4238/2015.december.29.46
|View full text |Cite
|
Sign up to set email alerts
|

Linker length affects expression and bioactivity of the onconase fusion protein in Pichia pastoris

Abstract: ABSTRACT. The aim of this study was to analyze the effect of linker length on the expression and biological activity of recombinant protein onconase (ONC) in fusion with human serum albumin (HSA) in Pichia pastoris. Four flexible linkers with different lengths namely Linker L0, L1: (GGGGS) 1 , L2: (GGGGS) 2 , and L3:(GGGGS) 3 were inserted into the fusion gene and referred to as HSA-n-ONC, where N = 0, 5, 10, or 15. The sequence of the fusion gene HSA-ONC was designed based on the GC content and codon bias in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The GSA linker (GSAGSAAGSG) is rich in glycine and serine residues, and a similar linker, GSAGSAAGSGEF, has been employed to ensure correct folding of GFP and associated fusion proteins . Since both the NL and GSA linkers are flexible and Lst constructs containing these linkers presented almost the same structure, it appears that linker length may be crucial in Lst–linker–SiBP1 constructs, a phenomenon reported with other proteins. ,, The difference in the length of the 16-residue NL linker and the 10-residue GSA linker was reflected in the observed differences in the size of the loop formed at the insertion point in the homology models (Figure ). The extra six amino acids in NL may provide additional space between Lst and SiBP1, making the LBD less affected by the rigidity of SiBP1.…”
Section: Discussionmentioning
confidence: 97%
“…The GSA linker (GSAGSAAGSG) is rich in glycine and serine residues, and a similar linker, GSAGSAAGSGEF, has been employed to ensure correct folding of GFP and associated fusion proteins . Since both the NL and GSA linkers are flexible and Lst constructs containing these linkers presented almost the same structure, it appears that linker length may be crucial in Lst–linker–SiBP1 constructs, a phenomenon reported with other proteins. ,, The difference in the length of the 16-residue NL linker and the 10-residue GSA linker was reflected in the observed differences in the size of the loop formed at the insertion point in the homology models (Figure ). The extra six amino acids in NL may provide additional space between Lst and SiBP1, making the LBD less affected by the rigidity of SiBP1.…”
Section: Discussionmentioning
confidence: 97%
“…However, misfolding or inappropriate protein interactions may destabilize protein structures and affect activity levels (Hong et al 2006 ). Our previous investigation, we found that inapposite assembly owing to the spatial interference of the element domain may result in the loss of activity in the end-to-end fusion protein (Karp and Oker-Blom 1999 ; Hong et al 2006 ; Yang et al 2015 ). The construction of insertion fusion protein has a significant potential value in catalytic regulation and biosensors (Ataka and Pieribone 2002 ; Ribeiro et al 2019 ).…”
Section: Strategies Of Enzyme Immobilization Mediated By a Scaffoldmentioning
confidence: 99%
“…Factors such as flexibility, composition, conformation, length, and hydrophilicity of the amino acid should be considered when selecting a linker for the fusion proteins (Robinson and Sauer 1998 ; Arai R, 2001 ; Chen et al 2013b ; Fan et al 2015 ; Yang et al 2015 ; Li et al 2016 ; Huang et al 2021 ). According to the flexibility of the linker, they can be divided into flexible linkers and rigid linkers (Fig.…”
Section: Design and Selection Of Linker Between The Fusion Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression level of the fusion proteins had no relationship with the linker length. However, while the ONC moiety of the fusion protein without a linker (n = 0) showed no cytotoxicity toward tumor cells, this gradually improved with increasing linker length [338]. …”
Section: Biomolecular Engineering For Nanobio/bionanotechnologymentioning
confidence: 99%